Analisis Parameter Fisik Vermikompos Menggunakan Cacing Lumbricus Rubellus, Limbah Baglog Jamur, dan Kotoran Kambing - Vian Dwi Chalisty; Ibnu Ubaidillah; Nunur Nuraeni (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Vermicomposting technology utilizes earthworms to decompose organic matter, producing worm manure (vermicompost) that contains essential nutrients, enzymes, vitamins, and microorganisms beneficial for plant growth as fertilizers. The tools used in this study included tarpaulins, trays, pH meters, soil meters, thermometers, and scales. The materials used in this study included Lumbricus rubellus worms, Javanese goat manure, mushroom baglog waste, and lime. The mixture of lime, baglog waste, and goat manure was fermented aerobically for 7 days. After that, 20 grams of earthworms were added to the media and maintained for 40 days, with the media being turned over on the 30th day. This study used 6 treatments and 3 replications: P0 (control, 5 kg baglog), P1 (4.5 kg mushroom baglog waste + 0.5 kg goat manure), P2 (4 kg mushroom baglog waste + 1 kg goat manure), P3 (3.5 kg mushroom baglog waste + 1.5 kg goat manure), P4 (3 kg mushroom baglog waste + 2 kg goat manure), and P5 (2.5 kg mushroom baglog waste + 2.5 kg goat manure). The parameters observed were pH, temperature, and particle size. Data were analyzed using a completely randomized design (CRD) with a one-way pattern, and Duncan's test was used for further analysis to identify significant differences. The results showed that the pH value of vermicompost in all treatments was the same, namely 8.5, and was not statistically significantly different (P > 0.05). All treatments had the same final temperature, specifically 28°C (P > 0.05). Treatment P5 showed the highest percentage of 20 mm sieve passability, at 99.60%, while treatments P0 and P1 had the lowest value, at 96.13%. This study concludes that overall treatments showed compost quality that met the standards, seen from the stable final temperature at 28°C, the final pH in all treatments of 8.5, and the particle size with the best results in treatment P5 (a mixture of 50% mushroom baglog and 50% goat manure) which achieved 20 mm sieve passability of 99.28%, so that treatment P5 was considered to produce vermicompost with the best physical quality.